(untitled) - Smith, Janice G. (Boston, 2008)
Smith's Organic Chemistry continues to breathe new life into the organic chemistry world. This student and instructor reviewed, new 2nd edition presents information in the form of bulleted lists and tables, with minimal use of text paragraphs. Janice Smith saw a great need for stepped-out worked examples; incorporated biological, medicinal, and environmental applications; and has built an art program that has yet to be seen in organic chemistry! Highlighting the art program are micro-to-macro art pieces that visually guide students to conceptually understand organic chemistry. Smith: Organic Chemistry is the text you need to see before making your organic chemistry decision.
Keywords: Chemistry, Organic,Hóa hữu cơ